(3fTb GdCRgGQ aj YLGFH GdCbWGQs - (3eMeO Hf CMeO Hf EjGS GdMfaj GdeUQj, CHh GdHQcGJ,J (B930 (3g` s
(3ChdgG (B:s
(3hHYO , aEfi deG WGdYJ cJH JhGQjN GdCee GdNGdjI aCMHHJ Cf CLeY cJGHkG dWjakG CPcQajg ef CYRH eG SeYJg hCYLH eG QCjJg bGUOkG ajg GdGNJUGQ s
(3BNQgG (B:s
(3hgPG BNQ efG GfJgi Edqi eeG LeYJg ai gPG GdcJGH hhbY Ydjg GdGNJjGQ ef GdCNHGQ hGdBKGQ hCYGf Gddg Ydi LeYg Edi Cf aQZ aj jhe GdLeYg GdeHGQc GdQGHY YTQ ef TYHGf SfI GKfJjf hYTQjf hJSYeGFI s
(3GfXQ Qbe (B1288 (3JGQjNs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B236s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B295 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B406 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B451 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs